Decoding Parkinson's Disease: The interplay of cell death pathways, oxidative stress, and therapeutic innovations - Tingting Liu; Xiangrui Kong; Junbo Qiao; Jianshe Wei (Redox Biology)
Parkinson's disease (PD), a complex neurodegenerative disorder characterized by selective loss of substantia nigra (SN) dopaminergic neurons, pathological aggregation of α-synuclein (α-syn), and chronic neuroinflammation, is fundamentally driven by redox imbalance and oxidative stress. Recent studies reveal that a dynamic interplay of programmed and non-programmed cell death mechanisms—amplified by oxidative damage—drives PD progression. Programmed cell death pathways include apoptosis (caspase-dependent mitochondrial/extrinsic pathways), necroptosis (eceptor-interacting serine/threonine-protein kinase 1 (RIPK1)/RIPK3/mixed lineage kinase domain-like protein (MLKL) axis), pyroptosis (NOD-like receptor thermal protein domain associated protein 3 (NLRP3) inflammasome/Gasdermin D (GSDMD)-mediated pore formation), PARthanatos (DNA damage-poly ADP-ribose polymerase (PARP-1)/apoptosis-inducing factor (AIF) cascade), ferroptosis (redox imbalance-driven lipid peroxidation/glutathione peroxidase 4 (GPX4) inactivation), disulfidptosis (disulfide stress from cystine metabolic collapse), and cuproptosis (mitochondrial lipoylated protein toxicity via copper-mediated oxidative damage), while non-programmed necrosis is triggered by energy collapse and calcium overload. Mitochondrial dysfunction, endoplasmic reticulum stress (ERS), and oxidative stress act as central redox hubs, integrating multiple death pathways through reactive oxygen species (ROS) bursts (O2·-, H2O2, ·OH), calcium dysregulation, and metabolic abnormalities, forming a self-amplifying vicious cycle. Non-neuronal cells (e.g., microglia and astrocytes) exacerbate neuronal redox damage by releasing pro-inflammatory cytokines (tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β)), dysregulating iron/copper metabolism (enhancing Fenton chemistry), and suppressing autophagic flux. Therapeutic strategies targeting redox-critical nodes include caspase/RIPK1 inhibition, GPX4 activators, autophagy modulators (rapamycin), acid β-glucocerebrosidase (GBA1) restoration, iron/copper chelators, and antioxidants (N-acetylcysteine) to restore glutathione homeostasis. Additionally, regulating glial polarization (triggering receptor expressed on myeloid cells 2 (TREM2) agonists) may disrupt inflammation-redox-death loops. Future challenges include deciphering spatiotemporal heterogeneity of cell death, developing multi-target redox therapies, and advancing biomarker-driven precision medicine (circulating free DNA (cfDNA), p-MLKL). Targeting redox dysregulation will guide breakthrough PD therapies.